Quality of Life and Mental Health Status Among Iranian Blue Workers With Self-Reported Chronic Low Back at 2015 - Amir Bahrami-Ahmadi; Mashallah Aghilinejad; Mohammad Hassan Nassiri-Kashani; Negar Aghili; Narges Shahnaghi; Elaheh Kabir-Mokamelkhah (Iranian Journal of Health, Safety and Environment, 2016)
Musculoskeletal disorders such as low back pain can cause a wide spectrum of chronic complications such as quality of life and general health impairment. Mental health is a wide spectrum of concepts that which those such as anxiety, depression or even quality of life had challengeable impacts on work related characters such as worker productivity, absensism. Present study was performed for evaluation of low back pain prevalence and its association with general health and quality of life status among blue workers of Fars ABFA Company. In the present study we focused on low back pain among 451 blue workers and assessed their mental health status and quality of life status with general health questionnaire (GHQ-28) and short form questionnaire (SF-36) respectively. In comparison one-year prevalence of low back pain was 44.2%. Mean of SF36 (63.90 ± 17.39 vs. 79.42 ± 15.01; P≤0.001) and General health subdomains (58.29 ± 19.63vs. 69.84 ± 18.63; P≤0.001) for workers with low back pain were significantly lower than other workers. Findings of our study showed that low back pain had impact on mental health status and quality of life among workers and these changes must consider in the designing preventive program more than control of pain.